Technology Adoption, Human Capital, and Sharia Accounting Literacy: Their Impact on Financial Reporting Quality - Ipuk Widayanti (Journal of Islamic Economics and Finance, 2025)
This research aims to determine the influence of understanding accounting, utilization of the Jurnal Id application, and human resource competence on the quality of financial reports at PT Era Cipta Digital in Medan City. This research uses independent variables, namely understanding of accounting, utilization of the ID journal financial application, and human resource competency. Meanwhile, the dependent variable is the quality of financial reports. This type of research is quantitative research using primary and secondary data. The sample from this research is all employees who work at PT Era Cipta Digital. In this research, the sampling technique used was the saturated sampling method. The statistical analysis used in this research is the classical assumption test, regression analysis, hypothesis testing using the T and F tests, and analysis of the coefficient of determination. Data collection was carried out using a questionnaire method which was distributed directly to 32 respondents. The results of this research indicate that the accounting understanding variable does not affect the quality of PT Era Cipta Digital's financial reports. The use of the ID journal application and HR competency has a positive and significant effect on the quality of PT Era Cipta Digital's financial reports.